Food-Related Quality of Life in Cancer Patients: Development and Validation of a Questionnaire. (7th June 2021) - Mercier, Catherine; Drareni, Kenza; Dougkas, Anestis; Farsi, Fadila; Funk-Debleds, Pamela; Roux, Pascal; Fingal, Chantal; Nazare, Julie Anne; Bensafi, Moustafa; Dayde, David; Mourier, Véronique; Giboreau, Agnès
Abstract: Objectives: Monitoring psychosocial, emotional, and hedonic aspects of food behavior is important to understand cancer patients' distress and help to reduce risks of malnutrition. However, to date, there is no specific tool to measure the impact of diet, eating behavior, and chemotherapy side effects on patients' food-related quality of life during cancer and its treatments. The objective was to develop and validate a questionnaire that aims to assess the food-related quality of life in cancer patients undergoing chemotherapy. Methods: Relevant items from the existing food-related quality of life assessment tools were selected to compose the present 46-item questionnaire. The validation of the questionnaire was conducted in 276 healthy volunteers and 173 cancer patients. Exploratory Factor Analysis (EFA) was performed in both groups, construct and discriminant validity, and test-retest reliability were calculated. Results: The questionnaire was perceived as clear and required less than14 minutes for completion (93% complete responses) in a pre-test ( n  = 156). The EFA allowed the inclusion of 9 dimensions in the food-related quality of life questionnaire. Common patterns between patients and healthy volunteers (factor loadings ≥ 0.4 in both groups) were used to calculate scores by dimension. Scores in the dimensions of adapting diet and sensorial discomfort (taste/odor) were higher in cancer patients, whilst scores in the dimension of discomfort in satiety were higher in healthy volunteers. Among patients with cancer, the total scores in sensorial discomfort, digestive discomfort, and discomfort in satiety were higher under chemotherapy than no treatment. Reproducibility after one week was in increasing order; digestive discomfort 0.6, adapting diet 0.61, products' quality 0.67, cooking 0.75, healthy diet 0.76, eating and pleasure 0.80, discomfort in satiety 0.82, and sensorial discomfort 0.85. Conclusions: This 46-item questionnaire can discriminate cancer patients versus healthy volunteers, and patients receiving vs those not receiving chemotherapy. A good to very good reproducibility was found for the most important factors of food-related quality of life of patients with cancer, i.e, eating and pleasure, sensorial discomfort, and discomfort in satiety. Funding Sources: This study is funded by La Région Auvergne Rhône-Aples and La Métropôle de Lyon.